Analisis Sistem Agribisnis di Mukomuko Sub Sektor Perikanan Tangkap Banyumas - Am Azbas Syukri; Gita Mulyasari; Mohamad Zulkarnain Yuliarso; Endang Sulistyowati (SMARTINDO, 2025)
Capture fisheries in Mukomuko are the main source of livelihood for the local fishing community. Mukomuko waters are one of the areas in Bengkulu Province with a coastline of 98.22 km. The potential of fisheries and marine in Mukomuko is certainly a great opportunity for poverty alleviation in the area. By developing local advantages and involving the local fishing community, it is hoped that the coastal area of Mukomuko can develop sustainably. The mission of the Mukomuko regent to make the area a center for agro-industry and agricultural trade can also support better local economic growth. The research method used is to utilize secondary data from the Mukomuko district marine and fisheries office and analysis of previous research results. Research materials include fisheries production, ship fleets, fishing gear, fishermen's conditions, and catches.